Motherhood and Space
XIV, 335 p.
Keywords: This is a collection of essays on the spatial dimensions of motherhood. Engaging both theoretical and empirical perspectives, contributors describe the intersection of space and gender across a variety of contexts with both familiar and unexpected territories explored.